Pengelolaan Tanaman Terpadu dan Teknologi Pilihan Petani: Kasus Sulawesi Selatan - Maintang Maintang (Iptek Tanaman Pangan, 2012)
Integrated Crop Management (ICM) is an approach in managing land, water, plant and pest in an integrated manner. The ICM had been implemented as a pilot model by the government to increase national rice production. To encourage further for its adoption by farmers, the Government launched the Integrated Crop Management Field School (ICMFS) since 2009. ICM emphasizing on farmers’ participation, site-specific technology, integration, synergy dynamic values and offers technology options as basic components and optional choices. In most areas generally ICM was reported as successful in increasing productivity of rice and more efficient in using production inputs. In South Sulawesi, field studies showed that farmers did not implement all components technology that was introduced as a whole. They had discretion in applying the technology, especially those which had impact on high productivity and easy to apply. For example, the application of organic fertilizer and planting using legowo pattern fell dramatically after farmers were no longer involved in the ICMFS. The unavailability of organic fertilizer and no apparent improvement in productivity from the use of organic fertilizer and the difficulty in applying a legowo pattern were the reasons that farmers were no longer apply the two components. Similarly with the intermittent irrigation, the use of LCC, and the planting young seedlings. This conditions need to be considered in the development of next ICM. Emphasizing two or three most effective components of technology on crop yields and easiness of its adoption seemed to have a greater attention than to encourage farmers to implement all components technology. The success of ICM was determined by the appropriateness of the technology selection and its application quality in the field.